Temperature-sensitive Steps in the Biosynthesis of Venezuelan Equine Encephalitis Virus - Zebovitz, Eugene (1967)
In contrast to Eastern equine encephalitis virus, the replication of Venezuelan equine encephalitis (VEE) virus was strongly inhibited at 44 C in chick embryo cells. The inhibited steps were analyzed by shifting the incubating temperatures up or down, and by determining during the shifts the rate and extent of infectious ribonucleic acid (RNA) synthesis, intact virus synthesis, and formation of complement-fixing antigen or of antigen detectable by a direct fluorescent-antibody technique. The inhibition appeared to be due to two temperature-sensitive steps involved in the synthesis of VEE virus in chick embryo cells. The first step of inhibition at 44 C occurred early in virus replication and could be completely reversed simply by transferring cultures to 37 C. The inhibition appeared to take place at some point between the time when the virus entered the cell and was uncoated and the beginning of viral RNA synthesis. The second temperature-sensitive step in VEE virus synthesis was irreversible; it occurred at a point after the synthesis of viral RNA, and before the formation of virus protein measured as complement-fixing antigen or as antigen that could be stained with fluorescent antibody.